US-Latin American relations in the 1990s: a new partnership for development and competitiveness: a Caribbean Basin proposal (FEDEPRICAP San JoseCR, 1992)
Reviews the results of the Caribbean Basin Economic Recovery Act (CBERA). Addresses issues raised in the US regarding wages and workers rights in the region. Analyses the issues of immigration, the environment and drug traffic. Looks at the impact of NAFTA on Caribbean Basin countries. Suggests also, that the Clinton Presidency has the opportunity to consolidate the trend toward more open economics in the region and transforms it into a far deeper comprehensive strategy linked to US industrial policy and international competitive strategy.
DC